Balance billing: the patients' perspective - Mathias Kifmann; Florian Scheuer (Health Economics Review, 2011)
We study the effects of balance billing, i.e., allowing physicians to charge a fee from patients in addition to the fee paid by Medicare. First, we show that on pure efficiency grounds the optimal Medicare fee under balance billing is zero. An active Medicare policy thus can only be justified when distributional concerns are accounted for. Extending the analysis by Glazer and McGuire, we therefore analyze the optimal policy from the patients' point of view. We demonstrate that, from the patients' perspective, a positive fee can be superior under balance billing. Furthermore, patient welfare can be lower if balance billing is prohibited. In particular, this is the case if the administrative costs of Medicare are large. However, we cannot rule out that prohibiting balance billing may be superior. Finally, we show that payer fee discrimination increases patient welfare if Medicare's administrative costs are high or if Medicare's optimal fee under balance billing implies lower quality for fee-only patients.
Keywords: I11; I18; H51; 330; physician reimbursement; price controls; Medicare